Engagement of coMmunity through Participatory learning and action for cOntrol and preVEntion of type II Diabetes and its Risk factors (EMPOWER-D) - A Protocol for a Cluster Randomised Controlled Trial - Rehman, Khalid; Tahir, Amber; Imtiaz, Sara; Khan, Zohaib; Afaq, Saima; Khan, Asima; Shah, Inayat; Kanaan, Mona; Sanauddin, Noor; Khaleeq, Nadia; Abdeali, Mariam; Walker, Simon; et al. (BMC public health, 2025)
Background In Pakistan, every third adult is suffering from diabetes. Community-based approaches have the potential to be effective in preventing diabetes. We aim to evaluate the effectiveness of a Participatory Learning and Action (PLA) intervention in the prevention and control of diabetes. Methods We will conduct a two-arm cluster randomised controlled-trial in two rural tehsils of district Swabi and district Peshawar in Pakistan. We will recruit 72 randomly selected clusters (the smallest official administrative unit in a tehsil) from two districts of the Khyber Pakhtunkhwa Province of Pakistan. From each cluster, 177 participants will be randomly selected for baseline and follow-up assessments, constituting a total sample size of 12,744. Following the baseline survey, the 72 clusters will be randomly allocated (1:1) to the intervention and control arms. The intervention arm will receive an 18-month long PLA intervention, including monthly community meetings where group members will identify, prioritise, and address problems associated with diabetes and the related risk factors. The primary outcomes of the trial are the prevalence of Type II Diabetes Mellitus (TIIDM), prevalence of Intermediate Hyperglycaemia (IHG), and 2-year cumulative incidence of TIIDM. Secondary outcomes include prevalence of hypertension, body mass index, abdominal obesity, prevalence of overweight & obesity, body fat composition, fruit and vegetable intake, physical activity, quality of life, psychological distress, knowledge of TIIDM risk factors, symptoms, & complications and self-awareness of diabetic status. Embedded economic and process evaluations will also be conducted. Ethics and dissemination The trial has received ethics approval from the National Bioethics Committee of Pakistan, and the ethics committees of The Aga Khan University, and Khyber Medical University. We will use a variety of channels, conferences, social media, dissemination events, and scientific publications to share the study findings with all the relevant stakeholders. Trial registration The trial is registered with clinicaltrials.gov—NCT06561126 . Date of registration: 23rd August 2024.